Assessment of Agricultural Practices for Controlling Fusarium and Mycotoxins Contamination on Maize Grains - Simões, Daniela (2023)
Funding Information: This research was funded by National Funds by Rural Development Program through the Operational Group QUALIMILHO—New sustainable integration strategies that guarantee quality and safety in the national maize, PDR2020 n° 101-031295 (2017–2020). This work was also supported by FCT, Portuguese Foundation for Science and Technology through the R&D Unit, UIDB/04551/2020 (GREEN-IT, Bioresources for Sustainability), the projects UIDB/00211/2020 and UIDB/04033/2020. Publisher Copyright: © 2023 by the authors.